Gasto público en salud y su relación con la mortalidad infantil: un análisis para el caso ecuatoriano usando técnicas de cointegración, período 1990-2022. - Vera Vega, Jeleny Cristhel (2025)
In 2022, approximately eleven out of every thousand live births in Ecuador did not survive their first year of life. This figure reflects the disparities and deficiencies in health systems, as well as in socioeconomic conditions, which primarily affect low-income families. Therefore, this paper aims to evaluate the relationship between public health spending and infant mortality in Ecuador during the period 1990-2022, using statistical and econometric techniques to propose strategies to help reduce this problem. The data used come from the World Bank, the Central Bank of Ecuador, and the Standardized Database on Global Income Inequality. The methodology used was the Vector Autoregressive model to identify the long-term relationships between variables and the Vector Error Correction model for the short term. In addition, cointegration techniques were used to identify the presence of causality between the variables. The results revealed a significant relationship, both in the short and long term, between both study variables, indicating that changes in public health spending are closely associated with changes in infant mortality; in turn, unidirectional causality was evident. Based on these findings, the national government was recommended to prioritize public spending on health and education, ensuring efficient and equitable distribution across different areas of the country in order to contribute to reducing the infant mortality rate.